2019
DOI: 10.1101/637702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Paraventricular Thalamus is a Critical Mediator of Top-down Control of Cue-motivated Behavior in Rats

Abstract: Stimuli or cues in the environment can elicit complex emotional states, and thereby maladaptive behavior, as a function of their ascribed value. Here we capture individual variation in the propensity to attribute motivational value to reward-cues using the signtracker/goal-tracker animal model. Goal-trackers attribute predictive value to rewardcues, and sign-trackers attribute both predictive and incentive value. Using chemogenetics and microdialysis, we show that, in sign-trackers, stimulation of the neuronal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…While the PrL-PVT pathway has been implicated in cue-reward learning [45,[55][56][57], the present study assessed the role of this pathway in mediating individual variation in cue-induced and cocaine-primed reinstatement of drug-seeking behavior. Sign-tracker and goal-tracker rats, categorized based on their propensity to attribute incentive salience to reward-paired cues, did not differ in behavior during cocaine self-administration [19][20][21]44] or extinction training prior to the reinstatement tests [19,22,44,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the PrL-PVT pathway has been implicated in cue-reward learning [45,[55][56][57], the present study assessed the role of this pathway in mediating individual variation in cue-induced and cocaine-primed reinstatement of drug-seeking behavior. Sign-tracker and goal-tracker rats, categorized based on their propensity to attribute incentive salience to reward-paired cues, did not differ in behavior during cocaine self-administration [19][20][21]44] or extinction training prior to the reinstatement tests [19,22,44,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The reported results challenge our hypothesis that the PrL-PVT pathway inhibits the incentive motivational value of reward cues. This hypothesis is based on our previous work that assessed the role of this pathway during Pavlovian learning [45], whereas the current study utilized an instrumental procedure. The neural circuitry mediating these two forms of associative learning are different [62][63][64][65]; thus, it is possible that the PrL-PVT pathway plays a distinct role in each of these forms of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVT has been implicated in a remarkably diverse range of functions including arousal (Colavito et al, 2015), stress (Bhatnagar, 2003;Bhatnagar and Dallman, 1999;Bhatnagar et al, 2002;Hsu et al, 2014), fear (Beas et al, 2018;Do-Monte et al, 2015;Penzo et al, 2015;Zhu et al, 2018), appetitive learning (Otis et al, 2017;Otis et al, 2019;Zhu et al, 2018), incentive salience (Campus et al, 2019;Haight and Flagel, 2014;Haight et al, 2015;Haight et al, 2017), relapse to drug seeking (Dayas et al, 2007;Dayas et al, 2008;Hamlin et al, 2009;James et al, 2011;James et al, 2010;James and Dayas, 2013;Marchant et al, 2010;Martin-Fardon and Boutrel, 2012;Matzeu et al, 2017;Matzeu et al, 2015), opiate withdrawal (Zhu et al, 2016) , drinking and feeding (Barson et al, 2015;Barson et al, 2017;Ong et al, 2017). We argue that PVT is implicated in these diverse functions because they have in common the need for motivational selection and PVT is a key component of the circuitry arbitrating this selection.…”
Section: Paraventricular Thalamus Manipulations and Behaviormentioning
confidence: 83%
“…As noted above, PVT is not necessary for approach to a lever or magazine (Choi et al, 2019;Choi and McNally, 2017;Do-Monte et al, 2017); but, when these behaviors compete with each other such as during sign-tracking, PVT is critical to selection between them. Under these conditions, PVT, and PL inputs to PVT, suppress approach to the lever (sign tracking) enabling approach to the magazine (goal tracking) (Campus et al, 2019;Haight et al, 2015). Flagel (Flagel et al, 2011;Haight and Flagel, 2014;Haight et al, 2017) has hypothesized that the opposite would be observed for hypothalamic inputs to PVT (i.e.…”
Section: Pvt and Conflict Within Motivational Systemsmentioning
confidence: 99%